Proximate composition of traditional vegetable and fruit based foods from Black Sea Area countries - Costa, H.S. (2012)
In the last years, there has been an increased consumers interest and demand for traditional foods, which have an important role in the diets. Traditional foods can also be a valuable contribution to the development and economic sustainability of rural areas and the preservation of biodiversity. The aim of this study was to determine the proximate composition in traditional vegetable and fruit based recipes from Black Sea Area countries, in the frame of the European Project BaSeFood. The determination of the nutritional composition of selected traditional foods from Bulgaria, Georgia, Romania, Russian Federation, Turkey and Ukraine is being carried out within the frame of the BaSeFood Project. Six foods from the vegetables group were analysed: Ukrainian borsch; Transcarpathian green borsch; Nettle sour soup; Nettles with walnut sauce; Rodopian dried beans and Kale soup. From the fruits group, five traditional foods were analysed: Uzvar; Plums jam; Churchkhela; Rose jam and Fruit of the evergreen cherry laurel. Water content, ash, total protein, total fat, total sugars and total dietary fibre are being determined at an accredited laboratory by ISO/IEC 17025 or by successful participation in Proficiency testing schemes. Most vegetable based foods have water and ash content higher than fruits. The values for water ranged from 14.2 to 92.4 g/100 g for Rose jam and Nettle sour soup, respectively. With respect to total fat content, generally fruit based foods have lower levels (< 0.15 g/100 g) than vegetables (5.02 g/100 g). For total protein, Nettles with walnut sauce presented the highest content (9.6 g /100 g) and Rose jam the lowest content (0.3 g/100 g). For total dietary fibre, the values varied between 0.3 and 6.44 g/100 g. All analytical values are expressed per 100 g of edible portion. The proximate composition of the selected traditional foods from Black Sea Area Countries is important in order to elucidate their role in the dietary pattern of populations. The analysed samples present a high moisture content and low fat content. Foods with high water content are usually low in calories. Therefore, vegetable and fruit based traditional foods are not energy dense foods, while they are considered rich in other essential nutrients.